GIBBSITE TYPE IDENTIFICATION FROM SOIL SAMPLE TO IDENTIFY HIGH-GRADE BAUXITE ZONE IN THE TAYAN AREA, WEST KALIMANTAN - P Y Simanjuntak, Yosafat
Bauxite is the main material used to produce aluminum products, formed from alumina-rich rocks. Exploration activities include various stages of mapping, from regional phase to detail mapping, to delineate alumina-rich rocks in the area. Intense weathering as commonly happened in tropical countries proved to be an obstacle in finding alumina-rich rock because they have been weathered into soils. These conditions often lead to ineffective results of test pit activity. Exploration vectors will play an important contribution in this manner to guide explorers in locating the high-grade test pit. In this context, this study attempted to learn vectors toward high-grade bauxite zones from the mineral assemblage and mineral parameters perspectives, using soil samples taken above the bauxite zone. The hypothesis is that variations in mineral assemblages/parameters can be used to distinguish differences in top soils above high-grade bauxite from medium and low-grade bauxite zones. A total of 84 test pits have been prepared in 5 different hills for this study in the research area. Two samples are taken from each pit, the soil sample is analyzed with spectral analysis to learn its mineralogy, and the bauxite sample is analyzed to obtain its alumina grade. These mineralogy and assay data are then being correlated to evaluate the mineralogy of the soil with their corresponding alumina grade. This research showed that there are two minerals identified from soil samples analyzed, they are kaolinite and gibbsite. Gibbsite characteristics revealed a positive correlation with variation in bauxite grade, unlike kaolinite whose characteristics showed no correlation with high or low-grade bauxite. There are four types of gibbsite revealed in this study, each type is correlated with very high, high, medium, and low-grade bauxite respectively. High-grade bauxite is characterized by A-type and B-type gibbsite while medium and low-grade bauxite are characterized by C-type and D-type gibbsite respectively.